WATERMELON YIELD AND EFFICIENCY OF USE OF WATER AND NITROGEN - Pereira, Laercio Da Silva [UNESP]; Da Silva, Everaldo Moreira; Piauilino Ferreira, Jose Orlando; Guerra Santos, Vinicius Lemos; Goncalves De Souza Lima, Carlos Jose; Da Silva Junior, Gabriel Barbosa (Univ Fed Rural Semi-arido-ufersa, 2019)
The evaluation of the yield of crops and their efficiency of use of water and nitrogen is essential to optimize the management of production factors. The objective of this study is to evaluate the effect of irrigation regimes and nitrogen doses in fertigation on fruit yield and efficiency of use of water and nitrogen by the Top Gun watermelon hybrid. The study was conducted in Bom Jesus, Piaui, Brazil, from August 4 to October 15, 2015. The study used a completed randomized block design with four repetitions, five irrigation depths (110.17, 156.86, 221.16, 268.87, and 317.09 mm), and five doses of nitrogen in fertigation (0, 50, 100, 150, and 200 kg ha(-1) applied as urea). Fruit yield and water use efficiency were not affected by nitrogen doses; however, there was a significant interaction of the factors for the efficiency of nitrogen use. The highest yield (39,549.45 kg ha(-1)) was obtained using 233.48 mm of water during the growth cycle. The water depth that promoted the maximum efficiency of water use was 110.42 mm, and nitrogen use was most efficient using 232.21 mm of water and 50 kg ha(-1) of nitrogen.
Keywords: Citrullus lanatus; Fertigation; Irrigation